Platelet-Rich Fibrin as a Bone Graft Material in Oral and Maxillofacial Bone Regeneration: Classification and Summary for Better Application. (6th December 2019) - Liu, Yiping; Sun, Xiaolin; Yu, Jize; Wang, Jia; Zhai, Peisong; Chen, Siyu; Liu, Manxuan; Zhou, Yanmin
Abstract : Platelet-rich fibrin (PRF) is an autologous platelet concentrate that consists of cytokines, platelets, leukocytes, and circulating stem cells. It has been considered to be effective in bone regeneration and is mainly used for oral and maxillofacial bone. Although currently the use of PRF is thought to support alveolar ridge preservation, there is a lack of evidence regarding the application of PRF in osteogenesis. In this paper, we will provide examples of PRF application, and we will also summarize different measures to improve the properties of PRF for achieving better osteogenesis. The effect of PRF as a bone graft material on osteogenesis based on laboratory investigations, animal tests, and clinical evaluations is first reviewed here. In vitro, PRF was able to stimulate cell proliferation, differentiation, migration, mineralization, and osteogenesis-related gene expression. Preclinical and clinical trials suggested that PRF alone may have a limited effect. To enlighten researchers, modified PRF graft materials are further reviewed, including PRF combined with other bone graft materials, PRF combined with drugs, and a new-type PRF. Finally, we will summarize the common shortcomings in the application of PRF that probably lead to application failure. Future scientists should avoid or solve these problems to achieve better regeneration.